2018
DOI: 10.1111/ecog.03315
|View full text |Cite
|
Sign up to set email alerts
|

Do joint species distribution models reliably detect interspecific interactions from co‐occurrence data in homogenous environments?

Abstract: Whether species interactions influence species response to environment and species ranges has always been a central question in ecology. Joint species distribution models (JSDMs) simultaneously model the species-environment relationships of multiple species and the residual correlation between these species. These residual correlations are assumed to depict whether species co-occur less or more often than expected by the modelled species-environment relationships, which could ultimately be attributed to specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
138
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(144 citation statements)
references
References 44 publications
6
138
0
Order By: Relevance
“…Joint species distribution models simultaneously estimate the species-environment relationship of multiple species and the residual correlation between those species that could be indicative of biotic interactions (Zurell, Pollock, & Thuiller, 2018), but also missing environmental information and other ecological processes. Similar to SDMs, JSDMs generate site-level occurrence probabilities of the different species, which have to be combined ("stacked") in order to yield predictions of local community composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joint species distribution models simultaneously estimate the species-environment relationship of multiple species and the residual correlation between those species that could be indicative of biotic interactions (Zurell, Pollock, & Thuiller, 2018), but also missing environmental information and other ecological processes. Similar to SDMs, JSDMs generate site-level occurrence probabilities of the different species, which have to be combined ("stacked") in order to yield predictions of local community composition.…”
Section: Introductionmentioning
confidence: 99%
“…Joint species distribution model (JSDM) estimates of environmental correlation (left) and residual correlation among tree species (right). Previous studies have shown that the signal of competitive interactions is more easily lost at increasingly coarser resolution than the signal of facilitative interactions(Araújo & Rozenfeld, 2014;Zurell et al, 2018). For ease of comparison, the same order was used for depicting residual correlation.…”
mentioning
confidence: 99%
“…Even with these improvements to JSDMs, separating environmental responses from competitive impacts is challenging (Adler et al, ), suggesting we should apply JSDMs to systems where the primary environmental drivers of species abundances are well understood (Giannini, Chapman, Saraiva, Alves‐dos‐Santos, & Biesmeijer, ; Wisz et al, ; Zurell, Pollock, & Thuiller, ). In grasslands around the world, non‐native plant species often increase in dominance at higher fertility sites and when grazing is excluded (Seabloom et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…competition) influence physiological tolerances to abiotic factors (e.g. However, simple formulations of these models should be used with care as they have been found to capture some biotic interaction types unreliably (Zurell et al 2018). One way to begin tackling these challenges at large spatiotemporal scales is to use joint species distribution models (SDMs).…”
Section: Joint Dynamic Species Distribution Modelsmentioning
confidence: 99%